Attitude towards aging and retirement from active apostolate of the sisters o.f Saint Paul De Chartres in the Philipines and in Korea - Jo , Cecilia
This study carried the main purpose of identifying the SPC sisters' attitude towards aging and retirement from active apostolate in Korea and in the Philippines. The specific objectives are:1. To assess the attitudes of sisters toward aging and retirement from active apostolate.